Plasma remediation technology for environmental protection - Du, ChangMing; Yan, JianHua (Advanced topics in science and technology in China., 2017)
This book introduces a new technology for environmental protection, namely plasma cleaning. It brings together technological advances in and research on plasma generators and their application in environmental science and engineering, including contaminated soil remediation, waste water degradation, metal recovery from waste solution, sterilization and polluted air remediation. The book provides a balanced and thorough treatment of the core principles, novel plasma reactors and diagnostics, and state-of-the-art environmental applications of plasma. As such, it represents a valuable reference guide for scientists, engineers and graduate students in the fields of environmental science and plasma physics.